Mechanical vapour compression desalination plant at Trombay. (20th November 2007) - Adak, A.K.; Kishore, G.; Srivastava, V.K.; Tewari, P.K.
Desalination plants based on Mechanical Vapour Compression (MVC) technology are inherently the most thermodynamically efficient. The thermodynamic efficiency of the MVC process is derived from the application of the heat pump principle. A single unit of a two-effect MVC desalination pilot plant of 50 m?/day capacity has recently been commissioned at Trombay, Mumbai. The desalination unit is very compact and unique in the seawater desalination technologies and is being operated by using electricity only. Horizontal tube thin-film spray desalination evaporators are used for efficient heat transfer. It is suitable for a site where feed water is highly saline and condenser cooling water is absent, and where a thermal heat source is not available. The unit produces high-quality water, nearly demineralised (DM) quality directly from seawater. There is no need for a polishing unit and product water can be used directly as make-up of boiler feed and for other high-quality process water requirements in industry. This paper includes the design and highlights the technical features of this unit.